Contending Worldviews in the Clinical Encounter: An Empirical Study of Complementary and Alternative Medicine Deliberations in Contemporary Medical Oncology - Kumbamu, Ashok (J Altern Complement Med, 2018)
Objective: In this article, the authors characterize the different ways patients and clinicians discuss complementary and alternative medicine (CAM) during routine cancer care. Methods: Over a period of two years, the authors audio-recorded clinical interactions between 37 medical oncology clinicians and a sample of 327 oncology patients at an academic cancer center in the Midwest United States. Recordings of conversations that included any discussion of CAM were transcribed and analyzed using a qualitative content analysis approach. Results: Out of 327 conversations, CAM was mentioned and/or discussed in only 31 encounters. Communication dynamics between clinician and patient involve several factors: the condition of the patient and his or her knowledge about and experience with CAM, the clinician's knowledge and values about CAM, perceived assumptions and stereotypes about CAM, and institutional response to the integration of CAM in cancer care. Conclusion: Addressing the difficult and sensitive topic of CAM in cancer care requires hearing patients in a manner meaningful to them. In that sense, CAM can serve as an important marker and test case in the march toward shared decision-making and patient-centered communication generally.